Avaliação de quatro genótipos de sorgo (Sorghum bicolor) com e sem taninos nos grãos para a produção de silagens - Daniel Ananias de Assis Pires (2007)
The objective of this work was to study the experimental period and the nutricional value of the silages of four genotypes of sorghum (CMSXS 165, CMSXS 114, BR 700 and BR 601), in assay of consumptionand apparent digestibility, as well as determining their chemical compositions and the nutritional value in in situ degradability assays and technique in vitro automatic production of gases, using itself ewes. Thedry matter (DM), crude protein (CP), fiber in neutral detergent (NDF), fiber in acid detergent (ADF) and crude energy (CE) determined in the silages had been of: 31.75, 32.04, 38.98 and 20.21%; 9.38, 9.03, 7.22 and 6.97%; 44.06, 47.87, 52.65 and 53.44%; 23.42, 26.23, 29.82 and 29.63% and 4368.45, 4321.95, 4317.56 and 4233.51kcal/kg, for the silages of genotypes CMSXS165, CMSXS114, BR700 and BR601, respectively. The consumptions of dry matter in g/unit of metabolic weight (DMI-MWU) had been of 51.05 and 51.23 g/MWU/day for the silages of CMSXS114 and CMSXS165, respectively. Already for the silages of hybrids BR700 and BR601 the consumptions of dry matter had been 28.37 and 33.57g/MWU/day, respectively. The values of apparent digestibility of the dry matter (ADDM), apparent digestibility of the crude protein (ADCP), apparent digestibility of the crude energy (ADCE) and apparentdigestibility of NDF and ADF of the silage CMSXS165 without tannin was higher (p<0,05) the values of voluntary consumption of the dry matter, crude energy, crude protein, and fibrous fractions. In the degradability study in situ the degradabilities of the dry matter 96 hours of incubation had varied of 57.10% for the silage of genotype BR601 to 73.19% for the silage of the CMSXS165. The effective degradability (ED) of the DM for the taxes of 2.0%/h, 5.0%/h and 8.0%/h had of 58.47, 49.87 and 46.12% for CMSXS165; 45.21, 37.97 and 35.39% for the BR601; 48.67, 41.83 and 38.49% for BR700 and 48.40, 41.19 and 38.04 for CMSXS114. The greatest potential of degradation (a) of the CP was found for the silage of CMSXS165 (79.88%). The taxes of degradation (c) of this fraction, the silage of the BR700, it presented the highest value of 4.67%/h. The degradabilities of NDF and ADF varied of 32.22 to 56.07% and 26.40 to 54.40%, for CMSXS165 and BR700, respectively. In the assay of production of gases the comparisons between the genotypes in the different periods of fermentation indicated that genotype CMSXS165 without tannin was that produced more gases. The values of DDM to 96 hours of fermentation was 69.20% for the silage of CMSXS165, 53.80% for the silage of CMSXS114, 55.6% for the silage of BR601 and 54.40% for the BR700, respectively. In the assay of production of gases thecomparisons between the genotypes in the different periods of fermentation indicated that genotype CMSXS165 without tannin was that produced more gases, being that the three last ones not differed(p>0.05) between itself. The maximum potentials of production of gases varied of 173 for the silage of the BR700 and 212 mL/g of DM for the silage of CMSXS165. The silage of CMSXS165 without tanninhiger than the others silages, in function of its potential greater of production of gases and effective degradabilities. The results conclude that the tannin in silages of sorghum compromise the exploration ofthe food for ruminants. Keywords: digestibility, nutritional value, sorghum, ruminant, silage, voluntary intake